(untitled) (Academia Science Repository, 2023)
This article is written about historical development of the several meanings in a single word. Thinking about meaning, language and it’s relation to the real and figurative word advanced enormously during the Renaissance, but real research into the multiplicity of meaning only began in the 18th century, with the study of neologisms, synonyms and the figures of speech.